2007
DOI: 10.1007/s00520-007-0263-6
|View full text |Cite
|
Sign up to set email alerts
|

An extended maintenance dosing regimen of epoetin alfa 80,000 U every 3 weeks in anemic patients with cancer receiving chemotherapy

Abstract: These results suggest that initiation of EPO 60,000 U SC QW is effective in the treatment of CIA and that EPO 80,000 U SC Q3W can be an effective extended dosing option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Given the low rates of transfusion in the randomized patients, consistent control of Hb in this study was achieved with epoetin‐α q3w, as reported previously in studies of qw dosing followed by q3w dosing8‐10 and studies that used more frequent administration of epoetin‐α throughout treatment 4, 5. Blood transfusion in the present study was more common among the nonrandomized patients (24%) than the randomized patients (8% to 9%).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Given the low rates of transfusion in the randomized patients, consistent control of Hb in this study was achieved with epoetin‐α q3w, as reported previously in studies of qw dosing followed by q3w dosing8‐10 and studies that used more frequent administration of epoetin‐α throughout treatment 4, 5. Blood transfusion in the present study was more common among the nonrandomized patients (24%) than the randomized patients (8% to 9%).…”
Section: Discussionsupporting
confidence: 81%
“…The majority of patients in that study had a Hb increase of at least 2 g/dL or achieved a Hb level of at least 12 g/dL. Recent prospective trials reported that initiating epoetin‐α at a dose of 40,000 or 60,000 U qw, and then extending the dose regimen to 80,000 or 120,000 U q3w, increased Hb and decreased transfusion requirements 8‐10. Initiating therapy with a q3w dose may be more convenient for the patient than starting with qw dosing and then extending the interval.…”
mentioning
confidence: 99%
“…A number of recent studies, including the study reported herein, have examined regimens combining a weekly initial dosing phase with an every-2-weeks or every-3-weeks EDP. [12][13][14][15] These studies consistently demonstrated that every-2-weeks or every-3-weeks extended dosing could maintain the hematologic benefits achieved with weekly initial dosing. Results from these studies led investigators to hypothesize that it might be possible to administer epoetin alfa at intervals less frequent than weekly at initiation of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Recent clinical data support extended dosing intervals (every 2 weeks or every 3 weeks) for epoetin alfa in this patient population. [12][13][14][15][16] The dosing flexibility of epoetin alfa in chemotherapy-induced anemia is underscored by pharmacokinetic data demonstrating a half-life of approximately 40 hours in anemic patients with cancer, whether administered at 150 U/kg 3 times weekly or 40,000 U weekly. 17 New epoetin alfa dosing schedules are needed for supportive care in patients treated with emerging chemotherapy regimens.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Given the challenges of adherence to complex medication regimens in HIV-infected patients, 12 it was anticipated that maintaining QOL and Hb levels with every other week dosing of epoetin alfa, after achieving a target Hb level with weekly dosing, would be more convenient. Less frequent dosing regimens have been investigated in cancer patients [13][14][15][16][17] and in patients with chronic kidney disease. 18 Based on these findings, the objectives of the present study were to evaluate the efficacy and safety of epoetin alfa administered subcutaneously (SC) at more prolonged intervals (every 2 weeks) in maintaining QOL and Hb in anemic HIV-infected patients.…”
Section: Introductionmentioning
confidence: 99%